2016
DOI: 10.3389/fpsyg.2016.00997
|View full text |Cite
|
Sign up to set email alerts
|

Causally-Rich Group Play: A Powerful Context for Building Preschoolers’ Vocabulary

Abstract: This work explores whether the facilitative effect of causal information on preschoolers’ word learning observed in the laboratory might be relevant to boosting children’s vocabulary in a group-play context. Forty-eight 3- to 4-year-old children learned six novel words for novel tools introduced during a small group-play session. Half of the groups used the tools according to their specified function to construct a fruit salad. The remaining children used the same tools to decorate a castle of blocks. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Confirming the generalizability of children's causal stance is important because attunement to causal information has developmental consequences (Mantzicopoulos et al, 2008;Stahl and Feigenson, 2015;Bauer et al, 2016). Perhaps most intuitively, interest in the causal properties of objects, and animals might be fundamental to children's engagement in scientific inquiry in both naturalistic and academic learning environments (Conezio and French, 2002;Legare, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Confirming the generalizability of children's causal stance is important because attunement to causal information has developmental consequences (Mantzicopoulos et al, 2008;Stahl and Feigenson, 2015;Bauer et al, 2016). Perhaps most intuitively, interest in the causal properties of objects, and animals might be fundamental to children's engagement in scientific inquiry in both naturalistic and academic learning environments (Conezio and French, 2002;Legare, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Bauer JR et al demonstrated the effectiveness of teaching by attention to group work as a useful method. 2 This research also discussed the results of small group learning and working with others. In some studies promotion of learning levels with new and suitable educational methods was emphasized.…”
Section: Discussionmentioning
confidence: 99%
“…Use of suitable educational methods plays a major role in education. 1,2 Medical sciences students should be read and translate specialized textbooks and journals and they need to learn and understand scientific language very well. 3,4 Some studies have shown the effectiveness of educational methods on students' learning.…”
Section: Introductionmentioning
confidence: 99%
“…Although identifying causal connections may be difficult (Sprites, Glymour, & Scheines, ), the benefits are worth the effort because understanding causal relationships improves our actionable knowledge (Johnson‐Laird, ) necessary for effective decision making (Sloman & Hagmayer, ) especially in business settings (Axelrod, ). Also, understanding causal relationships supports long‐term learning in children (Bauer et al, ).…”
Section: Existing Thinkingmentioning
confidence: 99%
“…In short, it seems to be increasingly accepted that theories are more useful when they indicate causal relationships (cf. Bauer, Booth, & McGroarty-Torres, 2016;Bryson, Ackermann, Eden, & Finn, 2004;Bureš, 2017;Deegan, 2011;Goodier, Austin, Soetanto, & Dainty, 2010;McGlashan, Johnstone, Creighton, de la Haye, & Allender, 2016;Panetti, Parmentola, Wallis, & Ferretti, 2018;Pearl, 2000;Sloman & Hagmayer, 2006;Waldmann, Holyoak, & Fratianne, 1995).…”
Section: Causalitymentioning
confidence: 99%